Bilateral Femoral Neuropathy: A Rare Complication of Drug Overdose due to Prolonged Posturing in Lithotomy Position - D. Tsiptsios; D. Daud; K. Tsamakis; E. Rizos; A. Anastadiadis; A. Cassidy (Case Reports in Neurological Medicine)
Background. Bilateral femoral neuropathy is an uncommon complication of various surgical and nonsurgical procedures, such as pelvic/abdominal surgery or vaginal delivery. Case Report. We report a case of a 41-year-old male who was found unresponsive against the wall in a “lithotomy-type” position with both knees flexed at approximately 90 degrees and both hips flexed and externally rotated at approximately 90 and 60 degrees, respectively, 24–48 hours after a drug overdose (combination of dihydrocodeine, paracetamol, diazepam, and amitriptyline). During his recovery, he complained of severe bilateral proximal lower limb weakness and bilateral distal lower limb pain and allodynia. His symptoms were initially attributed to critical illness myopathy/neuropathy (CIMN). However, thorough clinical and neurophysiological evaluation revealed that his symptoms were due to severe bilateral femoral neuropathies. Conclusions. To our knowledge, this is the first reported case of bilateral femoral nerve palsy due to prolonged posturing in a “lithotomy-type” position in the context of a drug overdose.